Metal Enolates – Enamines – Enol Ethers: How Do Enolate Equivalents Differ in Nucleophilic Reactivity? - Leonov, Artem I.; Timofeeva, Daria S.; Ofial, Armin R.; Mayr, Herbert (Synthesis, 2019)
The kinetics of the reactions of trimethylsilyl enol ethers and enamines (derived from deoxybenzoin, indane-1-one, and α-tetralone) with reference electrophiles (p-quinone methides, benzhydrylium and indolylbenzylium ions) were measured by conventional and stopped-flow photometry in acetonitrile at 20 °C. The resulting second-order rate constants were subjected to a least-squares minimization based on the correlation equation lg k = sN(N + E) for determining the reactivity descriptors N and sN of the silyl enol ethers and enamines. The relative reactivities of structurally analogous silyl enol ethers, enamines, and enolate anions towards carbon-centered electrophiles are determined as 1, 107, and 1014, respectively. A survey of synthetic applications of enolate ions and their synthetic equivalents shows that their behavior can be properly described by their nucleophilicity parameters, which therefore can be used for designing novel synthetic transformations.
Keywords: alkylation; enols; kinetics; linear free energy relationship; reactivity scales